Studying a gender responsive vaccine system: retrospective analysis of best methods - McKune, S.; Galiè, A.; Miller, B. A.; Bukachi, S. A.; Bikaako, W.; Pyburn, R. (Frontiers in Sustainable Food Systems, 2023)
Animal vaccines are essential for livelihood enhancement in Low-and Middle-Income Countries. Social and gender dynamics strongly affect who has access to, uses, and benefits from livestock vaccines. Yet, animal vaccine research has predominantly focused on the technical aspects of vaccine development, distribution, and adoption, with relatively limited attention paid to the socio-cultural circumstances that may affect vaccine adoption and utilization. Gender analysis in this context has been extremely limited. Utilizing the design and experiences of four projects funded to explore and improve gender responsive livestock vaccine systems, this methodological paper examines the performance of qualitative and quantitative research methods in understanding the essential elements of a fully functioning, gender responsive vaccine system: technical aspects (acumen/flow/ effectiveness), women's empowerment, policy environment, and gender norms. The article discusses the effectiveness of these methods for revealing and understanding the key features of gender responsive animal vaccine systems, as well as considering the shortcomings and opportunities that they offer.